Mercados de capital en America Latina y el Caribe, 1986 (Instituto Interamericano de Mercados de Capital CaracasVE, 1986)
Reviews regional and world economy. Discusses evolution in Region's primary and secondary value markets. Contains individual country reports which focus on the principal legal and institutional changes occuring in the capital markets during the year, and the financial policies adopted by each country.
IDS